A student proposal for ethical guidelines in anatomical education: Ethical and policy considerations. Issue 1 (19th November 2015) - Kahn, Peter A.; Gardin, Tova M.
Abstract : The recent publication of a story regarding anatomical dissection in a medical school has revealed the need for increased attention to the ethical and policy aspects of anatomical education. While most of the attention devoted to these questions thus far has been focused on procedures before and after dissection, from the perspective of medical students, there are important considerations during the process of dissection itself. This proposal was developed by two third‐year medical students through a review of the relevant published literature, reflection upon their personal experiences in anatomy courses in two separate institutions, and informal discussion of these topics with peers. The proposal is that basic ethical guidelines should be established and monitored by an independent committee tasked with reviewing them. The proposed guidelines include: First, a clear set of expectations about what the student is expected to learn with respect to anatomical knowledge and dissection technique; second, the establishment by schools or national bodies of minimal ethical standards regarding respectful behavior toward the donor bodies, and the communication of these standards to teachers and students involved in educational dissections; third, the use of materials that encourage students to view their donors with respect and ensure proper treatment of them; and fourth, the establishment of an oversight group (at each medical school and at national level) comprising students, faculty, community members, and staff, who will regularly review the anatomical education program and update these ethical guidelines as appropriate. While many of these proposals are already implemented in some anatomy departments, the establishment of clear guidelines at a national as well as a school‐by‐school level will permit students the freedom to participate fully in their education, knowing they have met the highest ethical standards as they prepare for a career as a humanistic physician. Clin. Anat. 29:60–64, 2016. © 2015 Wiley Periodicals, Inc.